Human tyrosine hydroxylase and insulin genes are contiguous on chromosome 11. - O'Malley, K L (1988)
The gene for the catecholamine biosynthetic enzyme, tyrosine hydroxylase (TH), has been previously mapped to human chromosome 11 p15.5 in the vicinity of the loci for insulin (INS) and for the oncogene Harvey Ras 1 (HRAS). Here we show that gene probes derived from recombinant clones containing either human TH or INS cross-hybridize with each other. Direct DNA sequencing demonstrates that these genes are physically linked on chromosome 11. The TH gene is 5' to INS and is separated by only 2.7 kb of flanking DNA. Both genes have the same transcriptional polarity and form a head-to-tail linkage group with insulin-like growth factor 2 (IGF-2) in the order: 5' - TH - INS - IGF-2 - 3'. Because of the close physical proximity of these genes, previously described polymorphisms for INS are identical to those observed with TH. The localization of TH to the highly polymorphic INS locus provides four new restriction fragment length polymorphisms which should help determine rapidly whether defects in TH are responsible for bipolar affective disorder in the Old Order Amish and other populations.